(untitled) (REVISTA NODO, 2015)
The public space and the landscape in Puerto Vallarta have been tied to the type of tourism that developed in the city (of the Sun and beach) same that he has placed to this city as one of the tourist destinations most visited of Mexico. This work realizes an analysis of the historical and social landscape of Malecón, public space of reference in this city, same that in the year 2011 surrendered to a process of restructuring with an intervention that gave to him a new image that is not very coincidental with that of Mexican people that historically it developed. This new pedestrian resultant walk corresponded more to the process of turistificación that it has followed the development of the city for more than one decade.